EFEKTIVITAS PEMBELAJARAN PAK DENGAN METODE TALKING STICK KELAS IV SD KANISIUS KURMOSARI SEMARANG - Winda Soladari Bago; Yustinus Joko Wahyu Yuniarto; Andarweni Astuti (Publisher STPKat, 2022)
The problem in this study is that the low student learning outcomes are caused by several factors, one of which is the use of inappropriate methods, where the method used is still using conventional methods with the help of printed books, causing students' motivation to take part in religious education learning is low and students tend to be passive during teaching and learning process in the classroom. In addition to the learning method factor, the responsibility factor also affects learning outcomes where student learning responsibility also looks low. From the data obtained from the homeroom teacher of SD Kanisius Kurmosari Semarang, it was found that more than 50% or half of the number of students who did not reach the KKM, namely 80. This study aims to determine the differences in student responsibilities who are taught using the talking stick method and without using the talking stick method to fourth grade students at SD Kurmosari Semarang. And To find out the average learning outcomes in increasing the effectiveness of learning by using the talking stick method in fourth grade students at SD Kurmosari Semarang. The method used in this study is a quantitative method using experimental research. The design used in this research is True Experimental Design. The results showed that there was a difference in the average responsibility of the experimental class students who used the talking stick method and the control class without the talking stick method, there was a positive influence of responsibility on learning outcomes and there were differences in the average learning outcomes of the experimental and control classes as well as amplified by the N-Gain test.